Effect of Ovariectomy on Orthodontic Tooth Movement in Rats - Mohammad Amin Mackie; Shahla Momeni Danaei; Salma Habibagahi; Nader Tanide; Ali Dehghani Najvani; Mostafa Montazeri (Islamic Dental Association of Iran, 2016)
Background and Aim: Estrogen affects the metabolism in females. This study aimed to assess the effect of absence of estrogen on orthodontic tooth movement in rats. Materials and Methods: In this animal study, 55 rats were randomly divided into four groups. Group 1 (n=10) had intact ovaries. In group 2 (n=15), ovaries were intact but the rats were subjected to stress due to tooth preparation. In group 3 (n=15), the ovaries were intact but the rats were subjected to stress due to tooth preparation and surgical manipulation. In group 4 (n=15), ovaries were removed and the rats were subjected to stress due to tooth preparation and surgical manipulation. Orthodontic appliances were placed after 14 days in groups 2 to 4. All groups except for group 1 were subjected to mesial movement of maxillary right first molar using NiTi closed coil spring applying 60g load for 21 days. The rats were sacrificed at 21 days and the amount of orthodontic tooth movement was measured using a feeler gauge. Data were analyzed using ANOVA. Results: The mean orthodontic tooth movement was 1.18±0.2 mm in group 4, which was significantly greater than that in group 3 (0.47±0.18 mm) and group 2 (0.22±0.07 mm) (P<0.001). Conclusion: Absence of estrogen can significantly accelerate orthodontic tooth movement in rats.